Epilepsy, behavior, and art (Epilepsy, Brain, and Mind, part 1) - Rektor, Ivan; Schachter, Steven C; Arzy, Shahar; Baloyannis, Stavros J; Bazil, Carl; Brázdil, Milan; Engel, Jerome; Helmstaedter, Gerhard; Hesdorffer, Dale C; Jones-Gotman, Marilyn; Kesner, Ladislav; Komárek, Vladimír; et al. (Epilepsy & behavior, 2013)
Epilepsy is both a disease of the brain and the mind. Brain diseases, structural and/or functional, underlie the appearance of epilepsy, but the notion of epilepsy is larger and cannot be reduced exclusively to the brain. We can therefore look at epilepsy from two angles. The first perspective is intrinsic: the etiology and pathophysiology, problems of therapy, impact on the brain networks, and the "mind" aspects of brain functions - cognitive, emotional, and affective. The second perspective is extrinsic: the social interactions of the person with epilepsy, the influence of the surrounding environment, and the influences of epilepsy on society. All these aspects reaching far beyond the pure biological nature of epilepsy have been the topics of two International Congresses of Epilepsy, Brain, and Mind that were held in Prague, Czech Republic, in 2010 and 2012 (the third Congress will be held in Brno, Czech Republic on April 3-5, 2014; www.epilepsy-brain-mind2014.eu). Here, we present the first of two papers with extended summaries of selected presentations of the 2012 Congress that focused on epilepsy, behavior, and art.
Keywords: umění; History, 16th Century; History, 17th Century; dějiny 20. století; Mental Disorders; Brain; History, 18th Century; Art; duševní poruchy; Behavior; dějiny 17. století; epilepsie; History, Ancient; chování; dějiny 16. století; dějiny starověku; lidé; History, 20th Century; dějiny 18. století; Humans; dějiny 19. století; History, 19th Century; History, Medieval; mozek; Epilepsy; dějiny středověku